Crystal structure of bis(benzyltrimethylammonium) tetrathiotungstate(VI), {(C6H5CH2)(CH3)3N}2[WS4] - Kim Kang-Woo; Kim Sunghyeon (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C20H32N2S4W, monoclinic, C2/c (no. 15), a = 37.4033(15) Å, b = 17.2676(7) Å, c = 16.4860(6) Å, β = 109.319(1)°, V = 10,048.2(7) Å3, Z = 16, Rgt(F) = 0.0422, wRref(F2) = 0.0930, T = 223 K.